Engaging men and boys in violence prevention - McInerney, William (In Factis Pax: Journal of Peace Education and Social Justice, 2019)
Review of Engaging men and boys in violence prevention. By Michael Flood, New York: Palgrave Macmillan, 2018, 392 pp., £34.08 (hardcover) ISBN 978-1-137-44210-9, £27.71 (ebook) ISBN 978-1-137-44208-6.